Deep Mining of Human Antibody Repertoires: Concepts, Methodologies, and Applications. Issue 10 (2nd September 2020) - Tian, Xiaolong; Li, Cheng; Wu, Yanling; Ying, Tianlei
Abstract: The ability of the human adaptive immune system to respond to antigens relies upon the tremendous diversity of T cell receptors (TCR) and B cell receptors (BCR). The entirety of an individual's BCRs, often referred to as an antibody repertoire, shapes the humoral immune system. Therefore, technologies to identify and characterize antibody repertoires are critical for understanding fundamental aspects of the development and maintenance of the humoral immune system. Recently, innovative methodologies and technologies devoted to high‐throughput sequencing of antibody repertoires (Ig‐Seq) have broadened the understanding of humoral immunity. This review provides an overview of the Ig‐Seq pipeline from sample collection, library preparation, and sequencing, to data cleaning, sequence alignment, and high‐level processing. Conventional and current strategies used in Ig‐Seq are introduced in detail, including bulk BCR sequencing, heavy and light chain paired sequencing combined with proteomic or single B cell sequencing approaches, antigen‐specific single B cell sequencing, and single‐molecule sequencing. Applications of Ig‐Seq are also discussed, including antibody diversity measurement, signatures associated with different populations, novel findings involved in the antibody repertoire development, and strategies of functional antibody discovery from antibody repertoires. Finally, the pitfalls and opportunities in the deep mining of antibody repertoires are discussed. Abstract : The entirety of an individual's B cell receptors, often referred to as an antibody repertoire, shapes the humoral immune system, and can be characterized by high‐throughput sequencing of antibody repertoires (Ig‐Seq). In this review, the overview of Ig‐Seq pipeline, various methodologies and applications, future directions and challenges in human antibody repertoire deep mining are discussed.